Social media in the newspaper newsroom : the professional use of Facebook and Twitter at Rapport and The Mail & Guardian - Jordaan, Marenet (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- Stellenbosch University, 2012.